Does the teaching-learning model based on the flipped classroom improve academic results of students at different educational levels? - Carmen González-Velasco; Isabel Feito-Ruiz; Marcos González-Fernández; José-Luis Á; Nicolás Sarmiento-Alonso (Universidad Complutense de Madrid, 2021)
The teaching-learning model that still predominates in higher education is the traditional one, based on the master class taught by the teacher. However, it is necessary to resort to other models of teaching and learning that are more flexible and active for students. For this reason, the main objective of this paper is to apply the flipped classroom teaching-learning model in order to test and compare if the academic results of students with the flipped classroom model improve with respect to the traditional model at different educational levels. In addition, the students' assessment of this teaching-learning model and the use of Information and Communication Technologies is analyzed. This study presents the experience of teaching innovation based on the inverted class model, which has been carried out with 155 students belonging to different educational levels and with six subjects related to the Financial Economics discipline. For this, a descriptive statistical analysis is performed, as well as analysis of contingency tables to detect the degree of association between the educational level and the teaching-learning model applied for the evaluation of the students. Evidence is obtained that university students obtain better academic results with the traditional model, while non-university students achieve better grades with the flipped classroom model. However, the students' assessment of the flipped classroom model has been very positive, regardless of educational level. The results suggest that the flipped classroom model improves the academic results of non-university students because they are more accustomed to the application of new technologies than university students.